Model Pembelajaran Mata Kuliah Keislaman Berbasis Masalah Komunitas Yang Terintegrasi Sebagai Langkah Menyikapi Merdeka Belajar dan Kampus Merdeka (MBKM) - Nasik, Khoirun (MADINAH, 2019)
The Policy of Merdeka belajar dan Kampus merdeka provides space for universities to have flexible authority in designing the tri dharma process to produce quality graduates. Students also have the opportunity to choose various activity programs which will later be converted into high credits. This article offers a learning model of a mix of Islamic subjects that is deemed inadequate to be implementative while integrating learning, research, and community service. This article provides a two-thing formula, addressing the policy of the ministry's MBKM program for free learning and an independent campus that requires practical-based learning innovations and departs from problems in order to create quality graduates. The integration that can be done to strengthen competence is the integration of two things, namely integral Tridharma (learning, research, and service) and integration across disciplines, across study programs and involving stakeholders.